Albendazole solid dispersions against alveolar echinococcosis: a pharmacotechnical strategy to improve the efficacy of the drug - Fabbri, Julia (2020)
Alveolar echinococcosis is a neglected parasitic zoonosis caused by Echinococcus multilocularis. The pharmacological treatment is based on albendazole (ABZ). However, the low water solubility of the drug produces a limited dissolution rate, with the consequent failure in the treatment of the disease. Solid dispersions are a successful pharmacotechnical strategy to improve the dissolution profile of poorly water-soluble drugs. The aim of this work was to determine the in vivo efficacy of ABZ solid dispersions using poloxamer 407 as a carrier (ABZ:P407 solid dispersions (SDs)) in the murine intraperitoneal infection model for secondary alveolar echinococcosis. In the chemoprophylactic efficacy study, the ABZ suspension, the ABZ:P407 SDs and the physical mixture of ABZ and poloxamer 407 showed a tendency to decrease the development of murine cysts, causing damage to the germinal layer. In the clinical efficacy study, the ABZ:P407 SDs produced a significant decrease in the weight of murine cysts. In addition, the SDs produced extensive damage to the germinal layer. The increase in the efficacy of ABZ could be due to the improvement of water solubility and wettability of the drug due to the surfactant nature of poloxamer 407. In conclusion, this study is the basis for further research. This pharmacotechnical strategy might in the future offer novel treatment alternatives for human alveolar echinococcosis.